Complete PET: Student's Book with answers - Heyderman E. Emma (Cambridge, Cambridge University Press, 2010)
Complete PET is a brand new course for the PET exam. It combines the very best in contemporary classroom practice with stimulating topics aimed at teenagers and young adults. I he course covers every part ot the Pe exam in detail providing preparation, practice, information and advice to ensure that students are fully prepared for every part of the exam. Informed by Cambridge's unique searchable database of real exam scripts, the Cambridge Learner Corpus*, and providing an official PET past exam paper from Cambridge ESOL, Complete PETis the most authentic PET exam preparation course available. Complete PET Student's Book with answers: contains 12 topic-based units. Each unit covers one part of each PET paper includes exercises targeting common PET candidate problem areas, using data from the Cambridge Learner Corpus includes an official past exam paper supplied by Cambridge ESOL the CD-ROM for Windows XP and Vista) contains additional practice not in the Student's Book, including skills, grammar, vocabulary and pronunciation the Writing and Speaking reference sections provide extra guidance for the Writing and Speaking papers contains a comprehensive Grammar reference section contains an answer key and recording scripts.Other components of this course: Student's Book without answers with CD-ROM Student's Book Pack Teacher's BookClass Audio CDs Workbook without answers with Audio CD Workbook with answers with Audio CD